2008
DOI: 10.3171/ped-08/01/048
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prophylaxis for surgical introduction of intracranial ventricular shunts: a systematic review

Abstract: Object Systemic antibiotics and antibiotic-impregnated shunt (AIS) systems are often used to prevent shunt infection. The authors conducted a systematic review to evaluate its effectiveness of antibiotics in patients who underwent placement of intracranial ventricular shunts. Methods The authors searched the Cochrane Central Register of Controlled Trials, MEDLINE, EMBASE, LILACS, and the meeting proceedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(45 citation statements)
references
References 30 publications
0
41
0
4
Order By: Relevance
“…There is good evidence that prophylactic antibiotics can reduce this rate, which unfortunately remains > 5% in most pediatric centers with its use. 18 Shunt infection is also related to age, with younger children manifesting higher infection rates. 6 Cerebrospinal fluid leakage, discussed above, is also a significant risk factor for shunt infection; therefore, meticulous attention to detail and especially to wound closure 13 is paramount.…”
Section: Discussionmentioning
confidence: 99%
“…There is good evidence that prophylactic antibiotics can reduce this rate, which unfortunately remains > 5% in most pediatric centers with its use. 18 Shunt infection is also related to age, with younger children manifesting higher infection rates. 6 Cerebrospinal fluid leakage, discussed above, is also a significant risk factor for shunt infection; therefore, meticulous attention to detail and especially to wound closure 13 is paramount.…”
Section: Discussionmentioning
confidence: 99%
“…28 The administration of preoperative antibiotic agents, typically those providing gram-positive coverage such as a first-generation cephalosporin, nafcillin, clindamycin, or vancomycin, has been demonstrated or is assumed to lower the infection rate for all major cranial and spinal neurosurgical procedures. [4][5][6] Numerous studies, including 3 meta-analyses, 21,24,29 have investigated the use of preoperative antibiotics as prophylaxis against shunt infection, both for adult and pediatric patients. Many of the original trials date back to the 1980s, and it is one of the few areas in neurosurgery in which there is an abundance of randomized controlled trials (RCTs).…”
mentioning
confidence: 99%
“…One of the most important actions shown to reduce shunt infections is perioperative prophylactic antibiotics, with the literature supporting their use in all patients undergoing a shunt insertion 2,24 . A systematic review and meta-analysis by Ratilal et al demonstrated that antibiotic prophylaxis can significantly decrease the rate of shunt infection (OR 0.51, 95% CI 0.36-0.73) 25 . Only 65% of the patients in our populations Antibiotics used per infection (n) 3 3-5 1 9…”
Section: Discussionmentioning
confidence: 99%